The Night of Tirakatan Tradition from an Islamic Perspective: An Anthropological Study in Karangploso, Piyungan - Siti Zahrah Nayogi; Nurhadi Nurhadi (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2026)
Purpose ̶ This study aims to describe the form and implementation of the malam tirakatan tradition in Karangploso Hamlet, Piyungan; to reveal its religious and socio-cultural meanings; and to analyze Islamic perspectives on its practice. Design/methods/approach ̶ Employing an anthropological approach with a descriptive qualitative method, data were collected through in-depth interviews with religious leaders, community figures, event organizers, and local residents. Findings ̶ The findings indicate that tirakatan is conducted collectively through communal cooperation, encompassing joint prayers, reflective sessions, speeches by community leaders, and shared meals. This tradition holds religious significance as an expression of gratitude and self-reflection (muhasabah), as well as social significance in strengthening solidarity and communal cohesion. Conclusion ̶ From an Islamic perspective, this practice does not contradict Islamic law as long as it is filled with acts that align with Islamic teachings. Therefore, the malam tirakatan tradition represents a form of living Islam, namely Islam as it is lived harmoniously, moderately, and humanely within local cultural contexts. Research Implication ̶ This study contributes conceptually to the advancement of culturally grounded Islamic studies rooted in local wisdom and recommends further research on the transformation of the tirakatan tradition and the practice of living Islam in diverse socio-cultural contexts across Indonesia.